Contribution Of Limb Muscle Power And Balance Of The Body To Front Kick Ability Of Pencak Silat Athletes Persaudaraan Setia Hati Terate Siak District: Kontribusi Power Otot Tungkai Dan Keseimbangan Tubuh Terhadap Kemampuan Tendangan Depan Atlet Pencak Silat Persaudaraan Setia Hati Terate Kecamatan Siak - Irfan Syah; Kamarudin Kamarudin; Ricky Fernando (Badnur Medisa Group, 2022)
The purpose of this research was to determine the contribution of leg muscle power and body balance to the front kick ability of the Setia Hati Terate Brotherhood Pencak Silat athlete, Siak District. The type of this research is multiple correlation. The population and sample in this study were the Pencak Silat Athletes of the Setia Hati Terate Brotherhood of Siak District, totaling 16 people. The research instrument used was a leg muscle power test with a standing broad jump and a body balance test with a stork stand and a pencak silat front kick test. Based on the results of the research, the conclusions obtained in this research are: (1) There is a contribution of leg muscle power to the ability of the front kick of the pencak silat athlete Setia Hati Terate Brotherhood of Siak District by 33.29% with an r count of 0.577 > r table 0.497, (2) There is a contribution the balance on the ability of the front kick of the pencak silat athlete of the Setia Hati Terate Brotherhood of Siak District by 31.58% with an r count of 0.562 > r table 0.497, (3) There is a contribution of leg muscle power and balance to the ability of the front kick of the pencak silat athlete of the Setia Hati Terate Brotherhood, Siak District of 52.71% with r count of 0.726 > r table of 0.497.